How plant diversity features change across ecological species groups? A case study of a temperate deciduous forest in northern Iran - FATEMEH BAZDID VAHDATI; SHAHRYAR SAEDI MEHRVARZ; ALIREZA NAQINEZHAD; HAMID GHOLIZADEH (Society for Indonesian Biodiversity, 2014)
Bazdid Vahdati F, Saeidi Mehrvarz Sh, Naqinezhad A, Gholizadeh H. 2014. How plant diversity features change across ecological species groups? A case study of a temperate deciduous forest in northern Iran. Biodiversitas 15: 31-38. Species diversity is one of the most important indices for evaluating the stability and productivity of forest ecosystems. The aim of this research was to recognize ecological species groups and to determine the relationship between environmental variables and the distribution of ecological species groups. For this purpose, 25 400-m 2 relevés were sampled using the Braun-Blanquet method. Vegetation was classified using modified Two-Way Indicator Species Analysis (TWINSPAN) and resulted in three ecological species groups. Different species diversity indices were applied to quantify diversity of these species groups. ANOVA and Duncan’s tests indicated that all species and environmental variables except altitude changed significantly across the species groups. The results also showed that the group located in the northern aspect and on low slopes had the highest diversity indices compared with groups located in dry aspects and on high slopes. In reality, abundant precipitation (northern aspect) and soil enrichment (low slopes) are principal factors that provide suitable conditions for plant growth and species diversity. Thus, the study of diversity changes in ecological species groups can result in an ecologically precise perspective for managing forest ecosystems.